(3YdGbI GdGQTGO GdfaSj GdQjGVj HGdGOGA GdQjGVj dOi dGYHGJ cQI GdSdI Ufa GcGHQ (B: (3ebGQHI JJeMhQ Mhd eMOOGJ GdGHYGO GdfaSjI s - (3Hf MehT, ahRjIs; (3Hf Ycj, eMfO Bcdjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3YfhGf GdOQGSI(B: (3YdGbI GdGQTGO GdfaSj GdQjGVj HGdCOGA GdQjGVj dOi dGYHGJ cQI GdSdI Ufa CcGHQ(B. (3gOaJ GdOQGSI(B: (3Edi eYQaI GSgGe GdGQTGO GdfaSj GdQjGVj aj JMbjb GdCOGA GdaYGd dOi dGYHGJ cQI GdSdI hYdGbI GdHYO GdeGOj HGdYedjI GdGQTGOjI, HGdEVGaI Edi YdGbI GdfJGFL GdeJMUd YdjgG HGdNOeGJ GdGQTGOjI hecGfI GdGQTGO GdfaSj aj GdHQfGeL GdJOQjHj deOQHj cQI GdSdI, CLQjJ GdOQGSI Ydi YjfI bhGegG (B59 (3dGYHI dcQI GdSdI daQb GdLRGFQ GdYGUeI, Je GNJjGQge HWQjbI bUOjI, hdLeY GdHjGfGJ GdNGUI HGdOQGSI, hddJMbb ef CgOGagG Je GSJNOGe GdefgL GdhUaj, dCfg edGFe hWHjYI GdehVhY, dcf ajeG jNU COhGJ LeY GdHjGfGJ GSJfOfG Edi GdcJH hGdeQGLY, HGdEVGaI Edi GSJNOGe GSJHjGf GdGQTGO GdfaSj GdQjGVj ef GYOGO GdHGMKI WHb Ydi GddGYHGJ, HGdEVGaI Edi ELQGA ebGHdI eY GdeOQHjf(B. (3JeJ GdeYGdLI GdEMUGFjI HGSJNOGe GdQReI GdEMUGFjI ddYdhe GdGLJeGYjI (Bspss(3, MjK LGAJ fJGFL GdOQGSI Ydi GdfMh GdJGdj(B: - (3jSge GdEQTGO GdfaSj aj JMbjb GdCOGA GdaYGd dOi dGYHGJ cQI GdSdI(B. - (3GdHYO GdeGOj dg OhQ cHjQ aj YedjI GdEQTGO GdfaSj dOi dGYHGJ cQI GdSdI(B. - (3jecf EQLGY GdfJGFL GdeMUd YdjgG ddaQjb Edi WHjYI GdNOeGJ GdEQTGOjI GdebOeI ef NdGd GdeOQH(B. - (3ddEQTGO GdfaSj GdQjGVj ecGfI cHjQI aj GdHQfGeL GdJOQjHj deOQHj cQI GdSdI hdg GfYcGS Ydi COGA GddGYHGJ(B. (3GdcdeGJ GdeaJGMjI(B: (3GdGQTGO GdfaSj GdQjGVj, GdGOGA GdQjGVj, cQI GdSdI, GdefGaSI(B. s
(3OcJhQGIs
Keywords: (3GdGOGA GdQjGVjs; (3GdGQTGO GdfaSj GdQjGVjs; (3GdGQTGO GdfaSj GdQjGVjs; (3GdefGaSIs; (3cQI GdSdIs